Development a Conceptual Framework for Industrial and Hazardous Wastes Rating Systems - Pourahmadi, Amirali; Ebadi, Taghi; Nikazar, Manouchehr (Salehan Institute of Higher Education, 2016)
Production of a large volume of industrial and hazardous waste with various compositions makes the need for comprehensive management and consequently the concept of waste rating more tangible. Despite numerous waste rating systems presented so far, analyzing the makeup of such systems play a significant role in meeting human health. In this study, the structure of 34 rating systems of industrial and hazardous waste have been analyzed based on both quantitative and qualitative standpoints and the results are presented as a formational-conceptual framework. Results showed that every rating system is formed of two parts of formational fundamentals and functional indices, which the first part has a longitudinal relation with the second. While lowly considered, this study is focusing on the formational fundamental part in the rating systems of industrial and hazardous waste, as intellectual prerequisites in suggesting a new system. Some of the factors in the first level are: dependence of the organization which determines the policy and general goals of a rating system, time of presenting the method during which remarkable changes take place in computing methods of the rating systems, infrastructures and facilities which are efficient in the accuracy and scope of the system and finally references and standards causing variations in definitions and final results of the rating system. Furthermore, factors such as: aspects of the study and style of use are identified in second level of formational fundamentals. Finally, the fundamentals are presented in a formational-conceptual framework for better perceiving and more effective use.